Spatial Modeling of Soil Salinity and Its Impact on Nutrient Availability and Agricultural Productivity - Meher, Kunal (Natural and Engineering Sciences, 2025)
The geographical variability of a variety of soil physical and chemical characteristics was investigated in agricultural regions with saline-alkaline soils. The characteristics that were analyzed included pH, magnesium (Mg), sodium (Na), exchangeable sodium percentage (ESP), sodium absorption ratio (SAR), bulk density (BD), calcium (Ca), available phosphorus (AP), available potassium (AK), electrical conductivity (EC), soil water content (WC), gypsum content, organic carbon (OC), and soil texture fractions. Soil samples were collected at five different depths (0–250 cm) at many places. To evaluate the geographical distribution of these soil qualities, the data were examined using geostatistical techniques, particularly semivariogram models. The results revealed significant spatial variability, with varying levels of spatial dependence across the research area. Electrical conductivity (EC) exhibited the highest spatial variability, highlighting its critical role in soil salinity and environmental pollution. pH and Available Potassium (AK), varied less throughout the research region. The spatial distribution of soil texture, SAR, and ESP exhibited strong spatial dependence. OC, BD, and Gypsum Content, however, showed moderate spatial dependence. The spatial dependencies of soil properties include external aspects, such as the composition of the bedrock, environmental pollution, agricultural pollution, drainage, and groundwater levels. Understanding these would be fundamental for assessing the impacts of salinization on the availability of nutrients and the productivity of agriculture.
uGDX
Keywords: Agricultural productivity; nutrient availability; soil salinity; spatial modeling; environmental pollution